A critical review of soil models and factors affecting earth retaining structures design - Abbas Jawad Al-Taie,; Mahmood Diab Ahmed, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Earth retaining structures, ERSs, are used in many engineering fields. Special considerations and technical knowledge in geotechnical engineering should be adopted in the modeling, analysis, and design of ERSs. Some of these considerations are related to the soil models, and (quality, settlement, and inclination) of the backfill and foundation soils of the retaining wall, RW, as presented in this critical review. This review shows that the analysis and design of ERSs are highly affected by model adopted for soil behavior, and the quality and characteristics of backfill materials. The backfill materials affect the selection of material type and performance of the ERSs, furthermore, they impact the soil interaction with RW. In selecting an appropriate model, it is important to consider the effect of soil history and stress changes that may the soil experience in the future. The design of some types of ERSs, backfilled with a material predominantly finer than the coarse sand grain size, should be conducted with precautions due to the possibility of lateral earth pressure (LEP) changing from active state to at-rest state after construction. It is worthwhile to consider both short-term and long-term settlements in the analysis and design of ERSs as there are specific types of ERSs that can tolerate large short-term settlements but cannot tolerate large long- term settlements. Finally, under both static and dynamic loadings, the angle of inclination of the backfill soil greatly affects the distribution of LEP and the value of the resultant force behind the RW.